A visit from the goon squad reread - Kreilkamp, Ivan (Rereadings, 2021)
"Jennifer Egan described her Pulitzer Prize-winning novel A Visit from the Goon Squad as a combination of Proust and The Sopranos. In rereading the book, Ivan Kreilkamp takes Egan up on her comparison, showing how it blends a concern with the status of the novel in the twenty-first century with an elegiac meditation on how we experience the passage of time. Kreilkamp, a former music critic, examines how Egan's characters turn to rock and especially punk in search of community and meaning. He considers what the novel's portrayal of music says about the role of art in contemporary culture as digitization makes older technologies obsolete. Combining personal and critical reflection, he reveals how A Visit from the Goon Squad articulates and responds to the sense of loss many feel as cherished physical objects are replaced with immaterial data. For Kreilkamp, Egan's novel compellingly combines the psychological realism of the nineteenth-century novel with more recent and transient forms such as the celebrity magazine profile or a PowerPoint presentation to provide a self-reflective diagnosis of the decay and endurance of literature. Arranged like Egan's novel into A and B sides, this book highlights not only how A Visit from the Goon Squad speaks to our mass-media and digital present but also its page-turning pleasure"--